2021
DOI: 10.1002/srin.202100179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impact Cavity Shape Induced by Supersonic Oxygen Jet on the Dynamic Characteristics of Molten Bath in Converter

Abstract: Figure 8. Effect of cavity shape on specific kinetic energy of molten bath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…The reasons for the formation of scattered cavities have been explained in detail in our previous study. [ 48 ] The slag–metal interface characteristics of the scattered cavities are significantly different from those of the overall cavity. It can be seen from Figure 3 that the majority of slag is blown away in the corner region of scattered cavities (Region B), where molten steel is exposed to the gas phase and accompanied by a large number of slag/metal droplets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the formation of scattered cavities have been explained in detail in our previous study. [ 48 ] The slag–metal interface characteristics of the scattered cavities are significantly different from those of the overall cavity. It can be seen from Figure 3 that the majority of slag is blown away in the corner region of scattered cavities (Region B), where molten steel is exposed to the gas phase and accompanied by a large number of slag/metal droplets.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the accuracy of supersonic jet velocity and cavity dimension, and the validity of the profile method have been verified in our previous studies. [46,48] 3. Results and Discussion…”
Section: Mesh Sensitivity and Model Reliability Validationmentioning
confidence: 99%
“…The depth of the cavity oscillated with time after 1.8 s, and the cavity depth fluctuated between 27.3 mm and 23.9 mm (mean 25.6 mm), as shown in Figure 5. The diameter (D) of the cavity changed synergistically with the depth [49,50], and remained relatively steady at about 135 ± 5 mm after 1.8 s. The variation law of cavities under the action of plasma arc jets has been shown in many studies on other jets impinging on a molten bath [48][49][50][51][52]. In order to clarify the formation mechanism of the cavity, the forces acting on the plasma arc-molten bath interface are schematically presented in Figure 6.…”
Section: Formation Processes Of Cavitymentioning
confidence: 95%
“…These results indicated that there was no steady state in the molten bath. This was because the net forces acting on the interface of the plasma arc and molten bath were in a dynamic equilibrium state [49,50]. After 80 s, the fluctuations in velocity at each point were relatively stable, as shown in Figure 7.…”
Section: Flow Field Of Molten Bathmentioning
confidence: 96%
See 1 more Smart Citation